Hyoliths with pedicles illuminate the origin of the brachiopod body plan. Issue 1887 (26th September 2018) - Sun, Haijing; Smith, Martin R.; Zeng, Han; Zhao, Fangchen; Li, Guoxiang; Zhu, Maoyan
Abstract : Hyoliths are a taxonomically problematic group of Palaeozoic lophotrochozoans that are among the first shelly fossils to appear in the Cambrian period. On the basis of their distinctive exoskeleton, hyoliths have historically been classified as a separate phylum with possible affinities to the molluscs, sipunculans or lophophorates—but their precise phylogenetic position remains uncertain. Here, we describe a new orthothecide hyolith from the Chengjiang Lagerstätte (Cambrian Series 2 Stage 3), Pedunculotheca diania Sun, Zhao et Zhu gen. et sp. nov., which exhibits a non-mineralized attachment structure that strikingly resembles the brachiopod pedicle—the first report of a peduncular organ in hyoliths. This organ establishes a sessile, suspension feeding ecology for these orthothecides and—together with other characteristics (e.g. bilaterally symmetrical bivalve shell enclosing a filtration chamber and the differentiation of cardinal areas)—identifies hyoliths as stem-group brachiopods. Our phylogenetic analysis indicates that both hyoliths and crown brachiopods derived from a tommotiid grade, and that the pedicle has a single origin within the brachiopod total group.